2007
DOI: 10.1369/jhc.6a7145.2007
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoglycan Subcomplex Expression in Normal Human Smooth Muscle

Abstract: The sarcoglycan complex (SGC) is a multimember transmembrane complex interacting with other members of the dystrophin–glycoprotein complex (DGC) to provide a mechanosignaling connection from the cytoskeleton to the extracellular matrix. The SGC consists of four proteins (α, β, γ, and δ). A fifth sarcoglycan subunit, ∊-sarcoglycan, shows a wider tissue distribution. Recently, a novel sarcoglycan, the ζ-sarcoglycan, has been identified. All reports about the structure of SGC showed a common assumption of a tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
4
28
0
Order By: Relevance
“…(iv) RhBGN restores the expression of DAPC components that are important for muscle integrity and function. (v) RhBGN could selectively target the tissues affected in DMD, as it binds to α-and γ-sarcoglycan (14), which are components of the dystrophin/ utrophin protein complex and are expressed selectively in heart and skeletal muscle (29)(30)(31)(32). (vi) RhBGN is well tolerated in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…(iv) RhBGN restores the expression of DAPC components that are important for muscle integrity and function. (v) RhBGN could selectively target the tissues affected in DMD, as it binds to α-and γ-sarcoglycan (14), which are components of the dystrophin/ utrophin protein complex and are expressed selectively in heart and skeletal muscle (29)(30)(31)(32). (vi) RhBGN is well tolerated in mdx mice.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous immunohistochemical and molecular studies on many sites of the human body, demonstrated that all sarcoglycans, with higher or lower expression, are expressed in human smooth muscle fibers hypothesizing the intriguing possibility of the existence of a pentameric arrangement of the SGC. The higher or lower expression of sarcoglycan subunits could be in conformity with the location and function of smooth muscle (14,27).…”
Section: Discussionmentioning
confidence: 84%
“…In the SMC, the dystroglycan complex (DGC) is associated with the sarcoglycan complex (SGC) (5)(6)(7)(8)(9)(10), in order to provide a mechano-signalling connection from the cytoskeleton-toextracellular matrix (ECM) in myocytes (11)(12)(13)(14). SGC plays a key role at the membrane and it is crucial in maintaining sarcolemma viability in muscle fiber membrane (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations